Act pro-childhood in and from the university in Manicaragua. Pedagogical conception (Cuadernos de Extensión Universitaria de la UNLPam, 2020)
The article proposes a pedagogical conception that enhances pro-childhood actionin its different contexts of action in Manicaragua. Its construction, in and from theuniversity, fosters transformations in the Cuban educational system in response tovulnerabilities related to family dysfunction, responsible for the occurrence of child abuse.Educational agents, such as teachers who are graduates or in training and outside theeducational sector, are trained through the municipal community pedagogical project For aHappy Childhood, the main setting where they get involved cooperatively. The spaces foranalysis, reflection, exchange, and decision-making that take place there generate amultiplicity of learning about preventive culture and rights, peaceful environments, well-being and satisfaction as an expression of happiness. These postulates of the conception areconsistent with the university-society articulation in its relationship with children, families,communities, the role of teaching and the determination of university content.
Keywords: pedagogical conception; act pro-childhood; educational agents; dysfunctional families; contexts.